THE STATE OF THE MICROCIRCULATORY BED IN DIABETIC FOOT SYNDROME WITH THE CARRIAGE OF VARIOUS VARIANTS OF THE T1565C POLYMORPHISM GENOTYPES OF THE ITGB3 GENE - Наталья Игоревна Троицкая; Константин Геннадьевич Шаповалов (Медицина в Кузбассе)
Purpose of the work – to study the state of the microvasculature in patients with the development of diabetic foot syndrome with various variants of carriage of the T1565C polymorphism genotypes of the ITGB3 gene.